Hubungan Motivasi Berprestasi dan Kecemasan terhadap Prestasi Atlet Usia Dini di SSB El Samba Purworejo - sudaryadi, mahmud; Setyawati, Heny (Universitas Negeri Semarang, 2023)
The focus of this research is the level of motivation and level of anxiety and the relationship between achievement motivation and anxiety on the achievement of young athletes at SSB El Samba Purworejo. The method used is correlational quantitative. The data collection technique uses a closed questionnaire instrument. The sample technique used is a total sampling of 40 athletes. The research results obtained (1) The level of achievement motivation with a value of 25%. (2) The level of anxiety is 40%. (3) The results of the relationship between achievement motivation and achievement obtained a sig value of 0.000. (4) The results of the relationship between anxiety and achievement obtained a sig value of 0.279. (5) The results of the relationship between motivation and anxiety towards achievement obtained a sig value of 0.128. Based on the results above, it can be concluded that (1) the level of achievement motivation is in the low category. (2) The level of anxiety is in the moderate category. (3) The results of the relationship between achievement motivation and achievement have a relationship. (4) The results of the relationship between anxiety and achievement have no relationship. (5) The results of the relationship between motivation and anxiety towards achievement have no relationship. The suggestions given by researchers are (1) athletes should maintain motivation and control exercise, (2) coaches should carry out structured training.